Macroscopic and microscopic characterization of mycoplasmosis in commercial chickens in Barishal, Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
Avian mycoplasmosis in commercial chicken is a serious problem around the world, and responsible for high economic losses and decreased poultry productivity. This study aimed to characterize the mycoplasma infection macroscopically and microscopically in commercially important poultry like broiler and layer in Barishal, Bangladesh. Diagnosis of mycoplasmosis was made on the basis of history, clinical signs, necropsy findings and histopathology of the suspected organs. The study was conducted on a total no. of 460 birds (broiler n=237; layer n=223) of 20 different farms of three different upazillas of Barishal district in Bangladesh. The overall prevalence of micoplasmosis was 26.52%. Layer chicken (30.04%) was more susceptible to mycoplasmosis than broiler chicken (23.20%). The highest prevalence of mycoplasmosis was observed in 3-6 weeks-aged chicken in both broiler (54.55%) and layer (35.82%) chicken. A significant difference (p